Trust and Health Care-Seeking Behavior - Michael E. Darden; Mario Macis (Institute of Labor Economics (IZA), 2024)
We present results from a nationally representative survey of American adults, guided by a simple theoretical model expressing health care-seeking behavior as a function of economic and behavioral fundamentals and highlighting the role of trust. We report several findings. First, we document a strong association between higher levels of trust in the health care system and reported care-seeking behavior, both retrospective and anticipated. This relationship holds across several care scenarios, from routine check-ups to vaccinations. Second, the impact of trust on health care utilization is similar in magnitude to that of factors such as income and education, long recognized as crucial in the existing literature. Third, the relationship between trust and care-seeking behavior appears to be mediated by key mechanisms from our theoretical framework, notably individuals' beliefs about the system's effectiveness in managing their health and their personal disutility tied to medical visits. Fourth, we ask respondents about trust in specific health care system sectors, and we find important heterogeneity in the associations between trust and care-seeking behavior, notably between trust in the Centers for Disease Control and Prevention and the likelihood to receive flu and COVID-19 vaccinations. Finally, we find no differential relationship between trust and care-seeking for Black respondents, but we find important differences by age and political affiliation. Our findings hold significant implications for policy, particularly given that trust in medical and, more broadly, scientific expertise is increasingly difficult to establish.
Keywords: I11; I12; I14; I18; 330; trust; health care; disparities